Development of a novel eye drop aid and evaluation of its efficacy - Yuka Kasai; Masako Sakamoto; Yuji Matsuda; Yuka Ito; Hirotaka Haro; Kenji Kashiwagi (PLoS ONE, 2025)
Purpose The aim of this study was to develop a new eye drop aid and investigate its efficacy in glaucoma patients. Methods The developed eye drop aid is compatible with most therapeutic eye drops and helps users with limited neck retroversion. Adult glaucoma patients admitted to the University of Yamanashi Hospital for glaucoma surgery who fulfilled the following criteria were included: a history of using glaucoma eye drops for at least 6 months, no upper limb loss or dysfunction, and no physical or cognitive disturbances that would interfere with activities of daily living. In terms of corrected visual acuity, the included patients had a logMAR score of at least 1 in at least one eye. Eye drops containing a 0.1% sodium hyaluronate ophthalmic mixture were used in this study. The eye drops were applied to the eyes in the seated position as they would normally be used. The use of the eye drop aid was explained, and the patients tried to instill eye drops with the eye drop aid after two trials. The patients then instilled one eye drop in the supine position, first without the eye drop aid and then with the eye drop aid. Success was defined as the eye drops being dropped into the conjunctival cul-de-sac without touching the ocular surface, face or eyelashes. The patients were surveyed about the usefulness of the eye drop aid. Although the aid was designed to require minimal grip force, we measured the force needed to dispense a single drop for five commonly used clinical eye drops. Results Eighty-eight patients were included (51 men and 37 women, mean age: 67.3 ± 13.4 years). The success rate in the seated position without the eye drop aid was 71.6%, and this rate decreased with increasing age; with the eye drop aid, the success rate improved significantly to 97.8%. The success rate in the supine position without the aid (86.4%) was significantly better than that in the seated position, and the eye drop aid increased the success rate to 97.8%. The eye drop aid reduced the squeeze force required to instill eye drops (reduction of 10.3%−53.5%) for all types of eye drops. Conclusion Even though the patients were accustomed to using glaucoma eye drops, 28.4% of the patients were not able to instill eye drops properly. The eye drop aid significantly improved the success rate of eye drop instillation, especially when the eye drops were administered while the patients were seated.